2010
DOI: 10.1007/s12566-010-0018-6
|View full text |Cite
|
Sign up to set email alerts
|

Protein glycosylation analysis with capillary-based electromigrative separation techniques

Abstract: An impressive complexity is associated with glycoproteins due to the microheterogeneity of glycosylation as posttranslational modification giving rise to a vast number of isoforms. The full characterization of glycoproteins is difficult to achieve, and a number of analytical methods have to be combined for a detailed understanding of glycosylation. In this review, we focus on capillary electromigrative separation techniques in the formats capillary electrophoresis, micellar electrokinetic chromatography, and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 193 publications
0
3
0
Order By: Relevance
“…Commonly used strategies for mass spectrometric IgG glycosylation profiling in proteolytic digests are RP and hydrophilic interaction LC coupled to MS (RPLC‐MS and HILIC‐MS) and direct mass spectrometric analysis of glycopeptides by MALDI‐MS . In recent years, CE‐MS has been applied for the analysis of glycopeptides from not only IgG but also erythropoietin proteolytic digests .…”
Section: Comparative Analysis Of a Standard Igg1 Glycopeptide Samplesmentioning
confidence: 99%
“…Commonly used strategies for mass spectrometric IgG glycosylation profiling in proteolytic digests are RP and hydrophilic interaction LC coupled to MS (RPLC‐MS and HILIC‐MS) and direct mass spectrometric analysis of glycopeptides by MALDI‐MS . In recent years, CE‐MS has been applied for the analysis of glycopeptides from not only IgG but also erythropoietin proteolytic digests .…”
Section: Comparative Analysis Of a Standard Igg1 Glycopeptide Samplesmentioning
confidence: 99%
“…Several examples of CE separations of glycans accomplished without mass spectrometric detection are described in the literature [33][34][35][36][37]. Most separations are performed under reversed polarity with a covalently modified capillary to suppress electroosmotic flow.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, these techniques are equipment intensive and require specialised skills. Therefore, several studies have been reported on the use of CZE with optical detection methods for routine analysis of glycoforms due to its high resolution, sensitivity, reduced analysis time and ease-of-use [23][24][25]. Taverna et al [26] propose that a strategy for CZE analysis of glycoconjugates is to try electrolytes at the pH extremes, to ensure that at least a single peak can be identified, followed by testing pHs closer to the isoelectric point of the glycoprotein to improve glycoform separation.…”
Section: Introductionmentioning
confidence: 99%